Kemampuan Numerasi Peserta Didik dalam Menyelesaikan Soal Asesmen Kompetensi pada Konten Aljabar di Kelas VIII SMP Anugerah Gloria Terpadu Wamena: Penelitian - Andinus Yanengga; Christine M Rumpaisum; Barthon Wenda; Marthinus Kayame (Jurnal Pustaka Cendekia Pendidikan, 2025)
This study aims to describe the numeracy skills of eighth-grade junior high school students in solving AKM problems with algebra content, identify the factors that influence them, and develop effective learning strategies to improve them. This study uses a qualitative approach with descriptive methods. The subjects of the study were eighth-grade students of Anugerah Gloria Terpadu Wamena Middle School in the 2024/2025 academic year. The main instrument in this study was the researcher herself, while the supporting instruments were test sheets and interview guidelines. This study used data collection techniques in the form of test techniques and interview techniques. The data analysis used three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the numeracy of eighth-grade students of Anugerah Gloria Terpadu Middle School is still categorized as low, due to the lack of explanation and reasoning of mathematical sentences in the problems. Therefore, improvements and development of mathematics learning are provided, such as the need to compile integrated learning materials between mathematical topics/concepts, everyday life, and other sciences to provide a relevant context for students. Because it coincides with curriculum adjustments to the development of the era. The curriculum in Indonesia will continue to change.